Influence of Hypertension on Longitudinal Changes in Brain Glucose Metabolism Was Modified by the APOE4 Allele Among Cognitively Normal Older Individuals - Zhou, Rui; Chen, Hao; Ye, Fanhao; Huang, Shiwei; Zhang, Jie (Frontiers in Aging Neuroscience, 2020)
Objective: To examine whether the influence of hypertension (HTN) status on longitudinal changes in brain glucose metabolism was modified by the apolipoprotein 4 (APOE4) status among older people with normal cognition. Methods: In this study, we included 217 older individuals with normal cognition from the Alzheimer’s Disease Neuroimaging Initiative (ADNI) study. Participants were divided into the HTN and no HTN groups based on self-reported medical history. Brain glucose metabolism was assessed by 18F-fluorodeoxyglucose-positron emission tomography (FDG-PET). Linear mixed model was fitted to examine the association between the HTN × APOE4 interaction and longitudinal changes in brain glucose metabolism after controlling for several covariates. Results: In the present study, we found that the association between HTN status and longitudinal changes in brain glucose metabolism varied as a function of the APOE4 status, such that the HTN/APOE4+ group showed a steeper decline in FDG SUVR than all other groups (No HTN/APOE4-, HTN/APOE4-, and No HTN/APOE4+). Nevertheless, there was no significant difference in the rate of decline in FDG SUVR among other groups (No HTN/APOE4-, HTN/APOE4-, and No HTN/APOE4+). Conclusion: The APOE4 genotype interacted with hypertension status to affect longitudinal changes in brain glucose metabolism among older individual with normal cognition, such that the HTN/APOE4+ group showed a steeper decline in FDG SUVR than other groups.